A fuzzy fault accommodation method for nuclear power plants under actuator stuck faults. (January 2022) - Wang, Pengfei; Jiang, Qingfeng; Zhang, Jiaxuan; Wan, Jiashuang; Wu, Shifa
Highlights: Fuzzy fault accommodation method is proposed for SPWRs under actuator stuck faults (ASFs). Fuzzy rules are set up to correlate target load and symptom variables under ASFs. The method adjusts target load dynamically to match reactor power under ASFs. Plant safety and stability can be ensured under ASFs using the method. Abstract: This paper proposes a fuzzy fault accommodation (FFA) method for nuclear power plants under actuator stuck faults. It can adjust the plant target load dynamically to match the reactor power during transients in which a few of the actuators lose their regulating capacity completely. The method was applied to a small pressurized water reactor (SPWR) under control rod driven mechanism and steam generator feedwater valve stuck faults. The obtained results demonstrate that the method can maintain balance well between the plant load and the reactor power under actuator stuck faults. Accordingly, the coolant average temperature and steam pressure of the SPWR can be restored to their constant setpoints without regulating the corresponding actuators, i.e., the control rods and the feedwater valves, demonstrating the effectiveness of the method. The research is expected to provide possible solutions for the reasonable and satisfactory control of NPPs under the dangerous actuator stuck faults.